1987
DOI: 10.1252/jcej.20.454
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of liquid-liquid phase mixing vessel.

Abstract: The scale-up effect of mixing vessels on the drop size of a liquid-liquid dispersion is discussed and correlative equations to estimate drop sizes in breakup and coalescence regions are proposed. It is shown that (n3d2D)(4Npln) is applicable as a scale-up standard and that the average energy dissipation rate, the Webernumberin the mixing vessel or the agitational Reynolds numberis not a satisfying scale-up standard. It is also shownthat the effect of volumefraction of dispersed phase on drop size is affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Another assumption made in the original model derivation by Narsimhan et al (1979) was a negligible effect of E on A. A general expression of the energy input per unit mass, E, for baffled and unbaffled systems is given by (Shuichi, 1958;Nishikawa et al, 1987): where P, E , N * , D,, D,, H , and K denote the power input (g.cm/s2), the average power input/unit mass (cm2/s3)), the impeller speed (s-I), the impeller and tank diameters (cm), the tank height (cm), and the power number (dimensionless), respectively.…”
Section: Theoretical Results and Discussionmentioning
confidence: 99%
“…Another assumption made in the original model derivation by Narsimhan et al (1979) was a negligible effect of E on A. A general expression of the energy input per unit mass, E, for baffled and unbaffled systems is given by (Shuichi, 1958;Nishikawa et al, 1987): where P, E , N * , D,, D,, H , and K denote the power input (g.cm/s2), the average power input/unit mass (cm2/s3)), the impeller speed (s-I), the impeller and tank diameters (cm), the tank height (cm), and the power number (dimensionless), respectively.…”
Section: Theoretical Results and Discussionmentioning
confidence: 99%
“…Scaleup of the Contactor. As for the scaleup of a liquid-liquid mixing vessel, Nishikawa et al (1987) recommended the use of the variable (4NP/ir)(n3cPD). This variable coincides with the average energy dissipation rate per unit mass of liquid in the mixing vessel when the vessel scale is fixed, and the dispersed phase fraction is kept constant.…”
Section: Resultsmentioning
confidence: 99%
“…Eckert et al (1985) reported that the impeller tip speed (nd) can have the controlling effect in drop formation. Nishikawa et al (1987) added that in such a case the impeller-to-vessel diameter ratio should also be taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…The proportional relation has been applied by most researchers to develop semiempirical d 32 correlations. The work to investigate the relation between d 32 and d max has been extended for different conditions where values of constant C at different conditions range between 0.38 and 0.70 as summarized by Zhou and Kresta (1997) . However, the authors did not support the linear proportional relation between d 32 and d max .…”
Section: Semiempirical Correlationsmentioning
confidence: 99%